2019
DOI: 10.18775/ijied.1849-7551-7020.2015.52.2004
|View full text |Cite
|
Sign up to set email alerts
|

Human Capital Spillovers and Human Development Index in Yogyakarta Special Region and Central Java

Abstract: This study analyzes the spillover of human capital in the Yogyakarta Special Region and Central Java. The research data includes the Human Development Index (HDI), capital, the ratio of college graduate workers, and the number of medical personnel in 2017 published by the Central Bureau of Statistics (BPS). This study uses a Spatial Regression analysis that includes elements of human capital spillover estimated by Geoda software. The results showed that there was a spillover of human capital between regencies/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 11 publications
(10 reference statements)
0
2
0
Order By: Relevance
“…The interaction might be in the form of people's migration, investment flow, and goods and service flow traded over areas. It can also be in the form of well-educated workers (Susanto & Welly Udjianto, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The interaction might be in the form of people's migration, investment flow, and goods and service flow traded over areas. It can also be in the form of well-educated workers (Susanto & Welly Udjianto, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The impact of spillovers not only increases human resources in local area, but also the surrounding area. The development of the economy in an area not only makes an increase in the prosperous population in the area, but also affects the welfare of the population in the surrounding area (Susanto & Welly Udjianto, 2019). Moretti (2004) explained the basis of the formation human capital spillovers from the view of spatial balance, which assumed that firms in urban areas are dependent on the overall level of human capital in cities, by comparing workers with higher education degrees in firms and cities.…”
Section: Introductionmentioning
confidence: 99%
“…(Irfan & Nooraeni, 2021) one of Indonesia's main characteristics of the demographic mega-trend phenomenon is the change in population mobility patterns from permanent to non-permanent. The primary purpose of people commuting is predominantly for work (Susanto & Welly Udjianto, 2019). Commuter travel can be interpreted as moving residents across the territorial border and back within a day (Irfan & Nooraeni, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Modeling with spatial regression, among others, is applied in criminology cases [8], human resources quality [9], even pollution [10]. Most study found that the spatial model can correct and improve the accuracy of classical linear regression modeling.…”
Section: Introductionmentioning
confidence: 99%